Parametric Analysis of the Toothed Electromagnetic Spring Based on the Finite Element Model - Xiaoyuan Zheng; Cheng Zhang; Yifang Lou; Guangming Xue; Hongbai Bai (Aerospace, 2023)
Active vibration control shows excellent performance in vibration isolation. In this work, the finite element model of a toothed electromagnetic spring (TES) is established using ANSYS Maxwell software. Subsequently, a static characteristic experiment of the TES is carried out, and the validity of the model is verified. Based on the established finite element model, the influence of key structural parameters on the static characteristics of the electromagnetic spring is analyzed. The results show that the parameters of the magnetic teeth have a significant impact on the performance of the electromagnetic spring. As the number of teeth increases, the electromagnetic force first increases and then decreases. With the increase in the tooth height or width, the maximum electromagnetic force gradually increases to the maximum value and then stabilizes. It should be noted that the tooth width simultaneously affects the maximum electromagnetic force, stiffness characteristics, and effective working range of the TES. This work provides a basis for further exploring the application of electromagnetic springs within the field of active vibration control.